Analysis and Simulation of Thermodynamic Diagrams of Convective and Destructive Storms in Mountainous Regions (Case Study: Meshkinshahr City) - Dariush Yarahmadi; Jamid Mirhashemi; Habib Ariantabar (جغرافیا و پایداری محیط)
Certain dynamic and thermodynamic conditions are required for the occurrence of precipitation. Sometimes, the intensity of the unusual operation and combination of these conditions causes severe precipitation, which usually occurs outside the perimeter and perimeter of the occurrence. Therefore, the environment cannot provide an optimal response to this abnormality and irreparable damage to the ecosystem. The July 29, 2001, precipitation is one of the most devastating events in Meshkinshahr. This caused a lot of financial losses, including the deaths of 33 people in the city. In this study, from the thermodynamic conditions of the atmosphere corresponding to this rainy day, the network data, temperature, geopotential height and relative humidity with a spatial resolution of 0.125 * 0.125 with steps of 25 and 50 hPa from 1000 to 200 hPa are used. Using the thermodynamic physical equations, the thermodynamic diagrams of the vertex column were simulated for a point with a width of 38.375 degree north and a length of 47.625 degrees east. The simulation of thermodynamic diagrams and calculation of physical indices with six hour time observation for this rainy day revealed that the most important factor in causing this rainfall is the different layering of humidity of the vertical layers, in which the potential temperature and equivalent potential temperature are higher than the hours before the beginning of precipitation to the beginning of precipitation, the trend is decreasing. These properties caused the formation of a hidden instability or potential during the hours prior to the start of precipitation, which, during the precipitation, was interchanged with the dynamic system and thermal convection, the instability of the potential turned into actual and caused the occurrence of flooding and destructive precipitation.